Students' scientific production in dental journals indexed in SciELO, 2018 and 2019 - Ibraín Enrique Corrales-Reyes; Katia Medalith Huamán-Castillón; Christian Renzo Aquino-Canchari; Bryan Alexis Cossio-Alva; Alberto Juan Dorta-Contreras (Editorial Ciencias Médicas, 2022)
Introduction: Publishing articles during undergraduate training makes it possible for students to complete the research process and develop skills useful for graduate education. Objective: Describe students' scientific production in dental journals indexed in the SciELO collection during the years 2018 and 2019. Methods: A cross-sectional observational descriptive study was conducted in which articles were the units of analysis. The journals considered were those indexed in the collection when the search was performed and those including articles containing information related to the academic degree of authors. The variables considered were journal name, impact factor, articles with students' participation, year of publication, languages, typologies, topics, number of students per article, authorship types and modes, countries, universities and citations. Results: Nine journals were evaluated, three of which did not contain any article of student authorship. A total 889 articles were published, with students participating in 3.49% of them. The International Journal of Odontostomatology (5.41%) was the journal with the largest number of articles of student authorship. 67.74% of the articles were original. Brazilian and Peruvian student authors published the same number of articles (n = 8). 19.35% of the articles dealt with topics related to maxillofacial surgery. Three articles were affiliated to the Peruvian National University of San Marcos. Conclusions: Students' scientific production is low in dental journals indexed in SciELO, and is mainly composed of original articles.